KEANEKARAGAMAN SUMBER DAYA HAYATI DAN POTENSINYA SEBAGAI BAHAN PESTISIDA NABATI - I Made Subrata (SEMBIO: Prosiding Seminar Nasional Biologi dan Pendidikan Biologi, 2024)
Indonesia is a tropical country that has a variety of soil types, types of climate, both macro and micro climates and other environmental factors, causing Indonesia to have a diversity of biological resources arranged in a high diversity of ecosystems, both natural and artificial ecosystems. Agriculture is an artificial ecosystem that functions to support the lives of farmers socio-economically. An agricultural ecosystem that is less stable will result in a decline in agricultural production and a decline in the health of people who consume agricultural products as the main food ingredient. In agricultural cultivation, controlling pests and plant diseases is absolutely necessary to increase agricultural yields. Vegetable pesticides are pesticides whose active ingredients come from plants or plants and other organic materials which are effective in controlling pest attacks and plant diseases. The ingredients for these vegetable pesticides are sourced from various types of existing plants. The active compounds in these botanical pesticides are biodegradable so they are safe for the health of the environment and consumers.